Cover Image. Issue 4 (23rd August 2018) - Tomita, Daichi; Suga, Tadashi; Ueno, Hiromasa; Miyake, Yuto; Otsuka, Mitsuo; Terada, Masafumi; Nagano, Akinori; Isaka, Tadao
Abstract : The cover image, by Daichi Tomita et al., is based on the Original Article Relationship between knee extensor moment arm and long‐sprint performance in male 400‐m sprinters, DOI: 10.1002/tsm2.33 .